Sociopolitical dimension of the teacher: a study of their relationship with the conceptions, professional training and experiences of a group of teachers - Téllez Fajardo, Alicia (Rastros Rostros, 2011)
The research “Concepts, approaches and educacional experiences of the table for quality of education in Floridablanca”, the sociopolitical dimension of the teacher was done in 2002 at the Universidad Industrial de Santander. Some teachers from the official sector of the department of Santander have different ways of organizing self-managed, self emerging, as the teachers are part of the tables for the quality of education which shows conceptions, result of their training and in their professional performance develop experiences in which socio-political dimension is evidenced. This study aimed to: analyze the components of educational ideas, approach es in the training and experiences that have contributed to the development of sociopolitical dimension of the teachers that make up the table for the quality of education of Floridablanca (mcef).